Peran Ibu sebagai Madrasah Pertama dalam Penanaman Karakter Anak - Siti Istatik Choiroyaroh (Mentari : Journal of Islamic Primary School, 2026)
This study analyzes the role of mothers as the first madrasah in instilling character in early childhood. A qualitative case study approach was employed, involving eight mothers with children aged 0-6 years in Tulungagung Regency, selected through purposive sampling. Data were collected through in-depth interviews, participant observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal three parenting styles: authoritative (4 mothers), authoritarian (2 mothers), and permissive (2 mothers). Mothers with authoritative parenting consistently implement five character instillation steps knowing the good, thinking the good, feeling the good, action the good, and habituating the good producing children with independence, discipline, responsibility, honesty, and religiosity. Authoritarian parenting yields fear-based compliance, while permissive parenting fails to establish discipline. Supporting factors include husband's support, quality time, and maternal understanding of child development. Inhibiting factors are uncontrolled gadget use, inconsistent grandparent intervention, and maternal fatigue. The study concludes that the mother's role as the first madrasah is crucial and requires family synergy. Character formation in early childhood is like carving on a gemstone requiring persistent effort for lifelong results.